PEMBELAJARAN MEMBACA NYARING TEKS BERAKSARA JAWA DENGAN MENGGUNAKAN METODE PEMBELAJARAN LANGSUNG PADA SISWA SEKOLAH DASAR - Maruti, Endang Sri (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2019)
The purpose of this study is to improve learning activities and student learning outcomes in learning the ability to read Javanese text using direct learning models in fourth grade elementary school students. This research is a Classroom Action Research (CAR) conducted in class IV SDN 01 Manguharjo, Madiun City with a total of 26 students. The method used to collect data in the form of observations, questionnaires, and tests. Data were analyzed descriptively qualitatively by the Milles Huberman flow method. The results of this study indicate that the percentage of students who complete learning with the direct learning method is 92.3% and 7.7% is incomplete. These results state that the completeness of learning material with the direct learning method has been successful, because it has reached a predetermined percentage of 80%. That way this direct learning method can improve the learning process and student learning outcomes in reading Javanese script